A Pilot Trial of Mindfulness Meditation Training for ADHD in Adulthood: Impact on Core Symptoms, Executive Functioning, and Emotion Dysregulation. (November 2017) - Mitchell, John T.; McIntyre, Elizabeth M.; English, Joseph S.; Dennis, Michelle F.; Beckham, Jean C.; Kollins, Scott H.
Objective: Mindfulness meditation training is garnering increasing empirical interest as an intervention for ADHD in adulthood, although no studies of mindfulness as a standalone treatment have included a sample composed entirely of adults with ADHD or a comparison group. The aim of this study was to assess the feasibility, acceptability, and preliminary efficacy of mindfulness meditation for ADHD, executive functioning (EF), and emotion dysregulation symptoms in an adult ADHD sample.Method: Adults with ADHD were stratified by ADHD medication status and otherwise randomized into an 8-week group-based mindfulness treatment ( n = 11) or waitlist group ( n = 9).Results: Treatment feasibility and acceptability were positive. In addition, self-reported ADHD and EF symptoms (assessed in the laboratory and ecological momentary assessment), clinician ratings of ADHD and EF symptoms, and self-reported emotion dysregulation improved for the treatment group relative to the waitlist group over time with large effect sizes. Improvement was not observed for EF tasks.Conclusion: Findings support preliminary treatment efficacy, though require larger trials.